Probing soot structure and electronic properties by optical spectroscopy. (1st January 2020) - De Falco, Gianluigi; Picca, Francesca; Commodo, Mario; Minutolo, Patrizia
Abstract: In this work, the physicochemical transformation of soot particles during the initial stages of formation and growth was investigated in a laminar premixed flame of ethylene and air. The selected flame condition allowed producing two classes of carbon nanoparticles, namely incipient and primary soot particles, on the basis of their size distribution. The two classes of particles have been selectively collected in well distinct flame zones for further chemico-physical characterization. The optical band gap decreases as particle size grows up. Particle medium range order and structure at molecular level have been investigated by Raman and fluorescence spectroscopy. Slight changes in particle composition were observed for incipient and primary soot. Both kinds of particles are made of a similar ensemble of fluorescence centers, which produce excitation dependent emission irrespective of particle sizes. In agreement with the Raman spectra, the molecular constituents of the particles are polyaromatic compounds with an average size of the order of ovalene molecules that only slightly increase from incipient to primary soot particles. These results suggest that the observed decrease of the optical band gap, as particle size increases, typical of a quantum-dot behavior, is not due to changes in particle composition at molecular level. Further investigations are needed to investigate possible evolution in supramolecular organization of the particles as they grow in flame and its effect on the optical band gap.